Contribution of Real Work Lecture Group 168 of UIN North Sumatra to the Life of the People of Gung Pinto Village, North Sumatra. - Ahmad Amin Dalimunte; Rizka Syahputri (Experimental Student Experiences, 2023)
The purpose of this research is to see the influence it has on the life of the people of Gung Pinto Village. The method used in this research is descriptive qualitative. The type of data used in this study is primary data with sources from the Village Head and the people of Gung Pinto Village. Data collection methods used in this research are interviews, documentation, and observation. The data processing technique carried out by the UINSU KKN 168 group uses data processing techniques from Miles and Huberman namely, data reduction, data presentation, and data verification. The work programs carried out in KKN activities, namely, socializing the dangers of drugs, socializing the importance of maintaining health and hygiene during a pandemic, counseling on making handsanitizers, processing waste into items that can be used and handicrafts, turning used bottles into trash cans and holding children's festivals sholeh or children's level competition.